Internet of Things based Data Acquisition and Controlling using ARM7 - K Sudheer Kumar Reedy , Dr. Srinivas Bachu , Kundeti Bhushan (International Journal of Advanced Science and Technology, 2020)
This research paper proposes the data Acquisition and Controlling System is one of the promising patterns in the time of processing in the present system automation industry and control. The proposed Paper is one such endeavor of planning on the web data acquisition and controlling framework utilizing ARM7. In this undertaking we have created ARM7 center with IoT to transmit the observed sensor information to the web. The System can finish the remote monitor and support activities of gear through the system utilizing an internet browser. By bringing the Internet into control organize, it is conceivable to get through the spatial, worldly limitation of conventional control arrange and successfully accomplish remote detecting, observing and continuous controlling of equipment. The principle substance of this task is to design and execute a Data acquisition and controlling System utilizing ARM7 and IoT association for modern controlling applications. The continuous simple voltages are changed over into relating computerized values utilizing the ADC pins inbuilt in LPC 2148 C and transfer to the IoT. In this paper are checking temperature in industry utilizing LM35 temperature sensor and Vibrations of machines utilizing Accelerometer sensor. Furthermore, we are additionally controlling the machine contingent upon the temperature.